Kesesakan yang Gaib : Kisah Perempuan Dayak Ngaju dalam Navigasi Kebakaran Hutan dan Lahan - Fadhila, Hanina Naura (Umbara, 2025)
The degradation of peat swamp forests that resulted in forest and land fires that hit Central Kalimantan in 1997, 2015, 2019, and 2023 was the beginning of the marginalization of women in its governance. Women lost their sources of food, clean water, and family livelihoods. As a result, women are faced with a confusion considering the burden of care that is pinned on them as a result of the gender division of labor in the family. But on the other hand, they are not equipped with sufficient knowledge in dealing with this problem. This research uses a feminist political ecology framework and ethnographic methods with Ngaju Dayak women living along the Katingan River to reveal the process of marginalization of women in disaster governance, especially in the aspects of disaster prevention and mitigation. The feminist political ecology framework helps to reveal the gendered dimensions of science, the right to live and work in a healthy environment, and the responsibility to protect the place of residence from all environmental hazards. The gender dimension that has been pinned and embodied to women is not considered in this matter. In addition, this approach must also recognize the political context referring to the way power constructs a gender narrative and the various policies that try to embody it through literature study. Women’s marginalization could be traced from the emergence of various intervention programs that introduced by the state and its auxiliaries and targeted the adjacent peat swamp forest community. Those interventions brought a further women’s marginalization and took a vantage point from the sociopolitical landscape alteration caused by mass forest fires.